2019
DOI: 10.1002/nau.24115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic techniques for apical organ prolapse repair – a systematic review of the literature

Abstract: Aims Apical defect is a pelvic organ prolapse disorder, with 5%‐15% prevalence. The aim of the study was to investigate methods of laparoscopic repair of apical defect and compare them with other techniques (open, vaginal, and robotic). Methods A systematic search of the literature was conducted in MEDLINE/PubMed and ClinicalTrials.gov databases using the following key words: apical prolapse and treatment procedures. The search was limited by using the humans filters. Only articles published in English between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
0
22
2
Order By: Relevance
“…The dissection method of LLMS is similar to that of ventral suspension in pectopexy, which fixes the descending organ to the iliopectineal ligaments using polyvinylidene fluoride monofilament mesh [14][15][16] . In a systematic review by Szymczak P and colleagues, pectopexy showed similar high patient satisfaction as sacrocolpopexy (96.4-97.6% vs. 71.0-100%), although long-term follow-up results are still required 17 . However, the operation field of pectopexy is surrounded by external iliac vessels and the obturator nerve.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dissection method of LLMS is similar to that of ventral suspension in pectopexy, which fixes the descending organ to the iliopectineal ligaments using polyvinylidene fluoride monofilament mesh [14][15][16] . In a systematic review by Szymczak P and colleagues, pectopexy showed similar high patient satisfaction as sacrocolpopexy (96.4-97.6% vs. 71.0-100%), although long-term follow-up results are still required 17 . However, the operation field of pectopexy is surrounded by external iliac vessels and the obturator nerve.…”
Section: Discussionmentioning
confidence: 98%
“…The round ligaments can also be folded to an ideal length during suturing if they are too long due to the stretching by descending organs, making tissue remodeling even better. This approach is very different from laparoscopic pectopexy or other types of lateral suspension using mesh, simply creating a new "mesh" ligament without augmentation of the original round ligament 17 . Female sexual dysfunction is common among women with urogynecological conditions 19 and should be managed with a multidisciplinary approach 20 .…”
Section: Discussionmentioning
confidence: 99%
“…LLS procedure is not indicated in the presence of a signi cant apical/posterior defect (enterocele, high rectocele) (16). When simultaneous anterior and posterior compartment repair was performed in the patients undergoing apical compartment defect repair, the risk of reoperation has reduced (17). Lateral arms performing suspension in cases used a T-shaped synthetic mesh graft in the LLS procedure do not ensure the closure of the pouch of Douglas.…”
Section: Discussionmentioning
confidence: 99%
“…The literature considers the sacralcolpopexy as the gold standard for vaginal vault prolapse, with a long-term success rates of > 90% and the most appropriate reconstruction of the physiological axis of the vagina [ 2 ]. Abdominal sacralcolpopexy has long been considered a safe and successful surgical procedure for the prolapse of the vaginal vault and has become the gold standard of care.…”
Section: Introductionmentioning
confidence: 99%